Effect of NPK Bio-Organomineral Dosage on Growth and Yield of Rice Plants on Industrial Waste Polluted Land - Pangestu, Catherine Febriana (Jurnal Solum, 2025)
Rice is a staple food in Indonesia and its production is crucial to meet the increasing demand. However, industrial pollution poses a threat to rice cultivation, particularly in the Rancaekek paddy fields. This study aimed to investigate the effect of NPK Bio-Organomineral fertilizer on the growth and yield of rice plants in industrially polluted land. The experiment was in September 2023-February 2024 and conducted in a greenhouse using Inpari 32 rice varieties. The research was set up in a randomized block design with eight treatments and four replications. The treatments consisted of: control (no fertilization), NPK 250 kg/ha, and NPK Bio-Organomineral treatment with doses of 125; 250; 375; 500; 625; 750 kg/ha. The results showed that the application of NPK Bio-Organomineral fertilizer increased the number of productive tillers, vegetative tillers, and grain dry weight. The optimal dose of NPK Bio-Organomineral fertilizer at a dose of 750 kg/ha showed the best results in increasing the number of vegetative tillers and productive tillers, while the dose of 375 kg/ha showed the best results economically in increasing the grain dry weight. This study shows that Bio-Organomineral NPK fertilizer can be an effective solution to improve soil fertility and increase rice yields on industrial waste polluted land.